2020
DOI: 10.1007/s40201-020-00548-y
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of disinfectants use and their adverse effects on the consumers after COVID-19 outbreak

Abstract: Background and objective The aim of this study was to investigate the pattern of disinfectants use within outbreak of COVID-19 and estimate their adverse effects on the consumer's health. Methods In this descriptive-analytical study, 1090 participants were entered into the study without age and gender limitations. A researcher-made electronic checklist containing 43 questions was applied to collect data. The checklist included three sections: demographic characteristics (8 questions), disinfection of body and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 38 publications
1
55
0
2
Order By: Relevance
“…The largest reported increases were for inhalation incidents, cleaning products with bleach, and disinfecting nonalcohol products and hand sanitizers, particularly in early in March 2020 when stay‐at‐home orders began. Related respiratory concerns, as well as dermatological complaints, have manifested in diverse geographic regions across the globe 74‐76 …”
Section: Introductionmentioning
confidence: 99%
“…The largest reported increases were for inhalation incidents, cleaning products with bleach, and disinfecting nonalcohol products and hand sanitizers, particularly in early in March 2020 when stay‐at‐home orders began. Related respiratory concerns, as well as dermatological complaints, have manifested in diverse geographic regions across the globe 74‐76 …”
Section: Introductionmentioning
confidence: 99%
“…35 In a descriptive study of 1090 Iranian participants, 87% of participants used the incorrect proportion of water and alcohol to make disinfectants at home and 42% experienced at least one disorder of their hands, feet, eyes, respiratory or gastrointestinal systems after sequential uses of disinfectants. 36 Furthermore, there are concerns that antibacterial hand sanitisers may contribute to antibiotic resistance in bacteria and loss of a barrier to protect against coronavirus. 37 In the report by Samara et al 33 it was suggested that the ideal disinfectant should have low toxicity profile with short- and long-term exposure, and that there is no safe chemical, so there is a need to enhance consumer awareness and develop disinfectants that are less harmful to humans and the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Sanitizer formulation containing tetrahydroxypropyl ethylenediamine has been known to be connected with occupational allergic contact dermatitis (Antelmi et al 2020). A study in the early phase of Covid-19 reveals episodic experiences one or other form of side effects on frequent hand washing and sanitization such as skin dryness, obsession, skin itching, coughing, and eye irritation (Dindarloo et al 2020).…”
Section: Health Hazards Due To Accompanying Ingredientsmentioning
confidence: 99%